HUBUNGAN POSISI DUDUK DAN LAMA DUDUK DENGAN KEJADIAN LOW BACK PAIN PADA PEGAWAI BIRO UNIVERSITAS ABULYATAMA - Abdul Wahab; Fuziati Fuziati (Jurnal Sains Riset, 2021)
Low back pain (LBP) is a pain sensation that is felt in the lower back which originates in the spine in the spinal area (lower back), muscles, nerves, or other structures in that part. The causes of LBP include: age, obesity (overweight), body mass index, pregnancy, and psychological factors. An older person will experience low back pain due to decreased body function, especially the bones, so that movement is no longer as elastic as when he was young. While the supporting factors for low back pain are posture errors such as: head bent forward, shoulders arched forward, abdomen protruding forward, and excessive lumbar lordosis can cause muscle spasm (muscle tension), this is the most common cause of low back pain. where the activities are done incorrectly or the ergonomics are wrong. The purpose of this study was to see whether there was a relationship between sitting position and sitting time with the incidence of low bac pain in the bureau staff at Abulyatama University, this study used an observational design with a cross sectional approach, the sampling technique in this study used purposive sampling where the sample was determined based on defined characteristics. This study showed a sitting position p-value of 0.299 (p 0.05) and a length of sitting p-value of 0.596 (p 0.05) indicating that sitting position and length of sitting had no relationship with low back pain.Keywords: Low back pain, sitting position, long sitting